A multicenter survey of re‐treatment with pegylated interferon plus ribavirin combination therapy for patients with chronic hepatitis C in Japan. Issue 1 (18th January 2013) - Oze, Tsugiko; Hiramatsu, Naoki; Mita, Eiji; Akuta, Norio; Sakamoto, Naoya; Nagano, Hiroaki; Itoh, Yoshito; Kaneko, Shuichi; Izumi, Namiki; Nomura, Hideyuki; Hayashi, Norio; Takehara, Tetsuo
<x xml:space="preserve">Abstract</x> Aim: This study aimed to clarify the factors associated the efficacy of re‐treatment with pegylated interferon (PEG IFN) plus ribavirin combination therapy for patients with chronic hepatitis C who had failed to respond to previous treatment. Methods: One hundred and forty‐three patients who had previously shown relapse (n = 79), non‐response (n = 34) or intolerance (n = 30) to PEG IFN plus ribavirin were re‐treated with PEG IFN plus ribavirin. Results: Twenty‐five patients with intolerance to previous treatment completed re‐treatment and the sustained virological response (SVR) rates were 55% and 80% for hepatitis C virus (HCV) genotype 1 and 2, respectively. On re‐treatment of the 113 patients who completed the previous treatment, the SVR rates were 48% and 63% for genotype 1 and 2, respectively. Relapse after previous treatment and a low baseline HCV RNA level on re‐treatment were associated with SVR in genotype 1 (P < 0.001). Patients with the interleukin‐28B major genotype responded significantly better and earlier to re‐treatment, but the difference in the SVR rate did not reach a significant level between the major and minor genotypes (P = 0.09). Extended treatment of 72 weeks raised the SVR rate among the patients who attained complete early virological response but not rapid virological response with re‐treatment (72 weeks, 73%, 16/22, vs 48 weeks, 38%, 5/13, P < 0.05). Conclusion: Relapse after previous treatment and a low baseline HCV RNA level have predictive values for a favorable response of PEG IFN plus ribavirin re‐treatment for HCV genotype 1 patients. Re‐treatment for 72 weeks may lead to clinical improvement for genotype 1 patients with complete early virological response and without rapid virological response on re‐treatment.